KENDHANGAN NARTOSABDAN PEMBENTUK KARAKTERISTIK GENDING SEMARANGAN - Risqia, Nanda Indah Nur; Suyoto, Suyoto (UI Scholars Hub, 2024)
The research aims to reveal the factors which contribute to the unique characteristics of Semarangan gending. Analysis involved four theories: Rahayu Supanggah’s garap theory, Stenberg’s creativity theory, C. A. van Peursen’s cultural development theory, and Marc Benamou’s rasa theory. There were three stages of data collection: literature study, observation, and interview. Results show three main characteristics of Semarangan gending: irama and laya, garap ricikan, and vocal garap. The tabuhan from this ricikan shows integration of musical styles from other areas, such as Yogyakarta, Banyumas, Surakarta, and East Java. In Semarangan gending, there are rasa of sigrak, prenès, and gobyog because of the support of gérong, keplok, and alok. To sum up, Semarangan gending has a high cultural value because it is widely enjoyed by both the art community and art consumers in general.